Outcome of Posterosuperior Based Flaps in Subtotal Tympanic Membrane Perforations - Aria Masoom, Abdul Manan Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tympanic membrane perforation is a major ear disorder that negatively affects the life of a person. Objective: The aim of this study was to find out the outcomes of Posterosuperior Based Flaps in Subtotal Tympanic Membrane Perforations. Material and methods: The current case series study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from August 2022 to January 2023 after taking approval from the research committee of the institute. A total of 104 individuals with chronic suppurative otitis media of tubotympanic type with dry central perforation were included. The individual provided written and informed consent. An x-ray of the sinuses, mastoids, and pure tone audiogram were performed. Each detail, including name, age, sex, and address, was noted. SPSS version 17 was used to analyze all of the data that was gathered. Results: A total of 104 cases were included in this study out of which 62 (59.6%) were female and 42(40.3%) were male. Most of the participants were in the age group 31-40 years old 22.1%. 51 individuals (82.2%) who had PS-based flap surgery reported improved hearing after receiving a graft, whereas 11 (17.7%) did not get a graft and continued to exhibit conductive hearing loss. In participants where the PS flap was not used, 32 (77.0%) had received a graft, whereas 10 (23%) had not and were deaf and had continuous discharge. Conclusion: The current study concluded that a posterior superior based flap in a subtotal perforation increases the blood flow to the graft center, improving the graft absorption rate and raising the success rate. Keywords: Outcome; Posterosuperior; Flaps; Subtotal Tympanic Membrane; Perforations